2017
DOI: 10.1002/met.1616
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the modulation effect of rainfall on solar radiation availability at the Earth's surface

Abstract: A significant proportion of the solar irradiance that reaches the Earth's surface is normally attenuated by atmospheric properties and overcast conditions related to the rainy season. The Solar Analyst (SA) model, irradiance and long term precipitation data were used to assess this relationship in Guadalajara, Mexico. A spatial analysis based on morphological and statistical criteria increased the model's certainty. The SA model explains 95.4% of the irradiation variability observed on the ground, with average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The atmospheric formation of quinones would occur both in the warm-dry and rainy seasons [27], since the MAG is located in a region with high exposure to solar radiation [28,29]. In fact, it has been suggested that solar radiation could favor the direct photolysis of the parent PAHs -Nap, Ant, and Phe [11].…”
Section: Correlation With Criteria Atmospheric Pollutantsmentioning
confidence: 99%
“…The atmospheric formation of quinones would occur both in the warm-dry and rainy seasons [27], since the MAG is located in a region with high exposure to solar radiation [28,29]. In fact, it has been suggested that solar radiation could favor the direct photolysis of the parent PAHs -Nap, Ant, and Phe [11].…”
Section: Correlation With Criteria Atmospheric Pollutantsmentioning
confidence: 99%
“…However, at present, cloudy and rainy weather and increasing number of haze events have aroused people’s concern; In addition, the net amount of radiation reaching the earth’s surface is falling 4 ). Sichuan is the largest industrial province in southwest China, there is a serious risk of air pollution that could mask or reflect radiation reaching the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the water-leaving irradiance reflectance in the spring and summer-fall seasons would be interpreted as the same; however, every season has different climatic conditions. The seasonal variations and similarities of the NIR-reflectance follow a normal behavior that matches with the incoming solar irradiation temporal pattern in this region, which is characterized by normal increases in the summer season [76]; nevertheless, the temporal randomness of the rain and cloud cover distribution affects the normality of the solar irradiation availability on the water surface. Therefore, each turbidity model was limited and probed upon image taken in the own season and close to the ground-sampling dates.…”
Section: Advantages and Challengesmentioning
confidence: 53%